Joint distribution of child mortality and wealth across 30 sub-Saharan African countries over 2000-2019 - Sato, Ryoko; Bolongaita, Sarah; Memirie, Solomon Tessema; Harttgen, Kenneth; De Neve, Jan-Walter; Verguet, Stéphane (Journal of global health, 2023)
Child mortality decreased remarkably over the last three decades, especially in low- and middle-income countries (LMICs) [1]. While the global under-five mortality rate dropped from 93 per 1000 live births in 1990 to 38 per 1000 in 2019, it was reduced from 178 per 1000 in 1990 to 78 per 1000 in 2019 in sub-Saharan […]
Gesehen am 05.12.2023